Impact of adjuvant endocrine therapy utilization in male patients with early breast cancer: results from a large German real-world claims data analysis - Dannehl, Dominik; Dijkstra, Tjeerd Maarten Hein; Au, Alexandra von; Scholz, Anna; Volmer, Léa; Hahn, Markus; Hawighorst, Sabine; Chaudhuri, Ariane; Ţăran, Florin-Andrei; Wallwiener, Markus; Bauer, Armin; Wallwiener, Diethelm; et al. (Archives of gynecology and obstetrics, 2025)
Male breast cancer (BC) is a rare entity and represents a significant clinical challenge due to its late diagnosis and resulting poorer prognosis compared to female BC. As shown by prior studies, approximately 99% of male BC patients are hormone receptor-positive (HR +). This study aimed to evaluate the utilization and impact of adjuvant endocrine therapy (ET) in male early BC patients using a large German real-world claims dataset.